The Transmission Mechanism for Monetary Policy in Developing Countries - Montiel, Peter (Washington, D.C. : International Monetary Fund, 1990)
In many developing countries the financial system is characterized by the absence of organized markets for securities and equities, by capital controls, and by legal ceilings on bank borrowing and lending rates, a situation which gives rise to parallel markets for foreign exchange and informal loan markets. This paper analyzes how changes in monetary policy instruments (bank credit, administered interest rates, required reserve ratios, and intervention in the parallel exchange market) are transmitted to domestic aggregate demand in a financially-repressed economy. Such an analysis is necessary to understand how the move to a more market-oriented system would affect the economy in the short run.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet